Factors influencing adoption of agro-ecological pest management options for mango fruit fly under information constraints: a two-part fractional regression approach - Owili, S. O.; Otieno, D. J.; Chimoita, E. L.; Baijukya, F. (Informa UK Limited, 2024)
The catalytic effect of climate change on the emergence and prevalence of invasive alien pests along with weak pesticide regulatory frameworks in developing countries calls for a transition towards sustainable pest management. Agro-ecological pest management (APM) offers a nature-based, cost-effective alternative for addressing systemic pest challenges, such as mango fruit fly invasion. We applied a two-part fractional regression to sequentially model APM adoption and intensity decisions among 423 smallholder mango orchard managers from Makueni County, Kenya. Despite APM’s potential, we observed moderate adoption rates (56.7%), with the average adopter implementing only 25% of the APM practices concurrently. Farmers’ socio-psychological attributes significantly influenced both adoption and intensity decisions. While perceptions of technology attributes and institutional and social factors primarily influenced both the adoption and intensity decisions, information constraints, resource endowment, gender and inter-generational factors significantly influenced only the intensity decision. To support the transition from synthetic insecticides to APM measures, policymakers should create more opportunities for awareness creation, training and knowledge co-creation and co-production, particularly through social networks and gender-disaggregated participatory group approaches.